A Review of Epidemiology of Viral Hemorrhagic Fever - Srivastav, Yash; Mansoori, Mohd. Faijan; Pandey, Vipin Kumar (Disease and Health Research - New Insights Vol. 1, 2024)
The pathophysiology, aetiology, diagnosis, treatment, symptoms, and indicators of virus hemorrhagic fevers (VHFs) are all covered in this review article. Acute zoonotic diseases known as viral hemorrhagic fevers (VHFs) initially appear to be related to platelet malfunction or destruction. The term "Viral Hemorrhagic Fever" (VHF) describes a severe feverish sickness characterized by aberrant vascular control, vascular damage, and hemorrhagic symptoms. Multiple viruses belonging to distinct families are the cause of this illness. The viruses that cause VHF are categorized into seven distinct families according to the International Committee on Taxonomy of Viruses' most recent classification: Hantaviridae, Nairoviridae, Filoviridae, Phenuiviridae, Paramyxoviridae, Arenavidae, and Flaviviridae are the families involved. The concept of virus hemorrhagic fevers (VHFs) originated in the 1930s when Soviet researchers were studying hantaviral hemorrhagic fever (HF) with renal dysfunction. Dengue fever/Dengue haemorrhagic fever and Kyasanur forest sickness are the two most common viral hemorrhagic fevers (VHF) in India, that are transmitted by arthropod vectors. There is currently no effective cure for VHFs. Some people have responded well to ribavirin treatment for Lassa fever or HFRS. The diagnosis of community-acquired pneumonia (CCHF) in India is greatly hampered by the co-occurring symptoms of hemorrhagic fevers such as dengue, Kyasanur forest sickness, Hantavirus hemorrhagic fever, and other illnesses such as leptospirosis, meningococcal infections, and malaria. The pathophysiologic features of VHF include microvascular instability, increased vascular permeability, and poor hemostasis, albeit the underlying processes differ depending on the virus. Additional randomized controlled studies are needed to find out more about the best way to treat viral hemorrhagic fevers (VHFs). We want to investigate viral hemorrhagic fevers (VHFs) further.